2007
DOI: 10.2478/v10001-007-0035-z
|View full text |Cite
|
Sign up to set email alerts
|

Personal Exposure to Fine Particles and Benzo[A]pyrene. Relation with Indoor and Outdoor Concentrations of these Pollutants in Kraków

Abstract: We conclude that although ambient PM(25) measurements provide an adequate indicator of outdoor air quality for use in epidemiologic studies, they may not be adequate for studies on relationship between non-ambient pollution and health effects. Since only about 20% of variability in personal B[a]P exposure could be explained by personal PM(25) level, the extrapolation of personal exposure to B[a]P from personal PM(25) data may be greatly underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…HDD refers to mean ambient temperature (18 °C) under which household heating is required for thermal comfort, and was calculated by subtracting averaged ambient temperature of given day from 18 °C (Silverberg et al, 2013). Regarding our second assumption of equal infiltration rate of the nine PAHs and PM 2.5 , our earlier analysis showed that PM 2.5 is likely to be a carrier for chrysene (Pearson’s rho correlation coefficient > 99%) (Jedrychowski et al, 2007). Furthermore, high mutual correlations of the eight c-PAHs (all Pearson’s rho correlation coefficient > 97%) suggest that the remaining eight particle-bound PAHs in this analysis are also carried by PM 2.5 (Choi et al, 2008a).…”
Section: Methodsmentioning
confidence: 99%
“…HDD refers to mean ambient temperature (18 °C) under which household heating is required for thermal comfort, and was calculated by subtracting averaged ambient temperature of given day from 18 °C (Silverberg et al, 2013). Regarding our second assumption of equal infiltration rate of the nine PAHs and PM 2.5 , our earlier analysis showed that PM 2.5 is likely to be a carrier for chrysene (Pearson’s rho correlation coefficient > 99%) (Jedrychowski et al, 2007). Furthermore, high mutual correlations of the eight c-PAHs (all Pearson’s rho correlation coefficient > 97%) suggest that the remaining eight particle-bound PAHs in this analysis are also carried by PM 2.5 (Choi et al, 2008a).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the exposure assessment based on 1-HP level in urine enabled analysing of several exposure sources (i.e. air pollution, smoking and diet) [1][2][3][9][10][11]. The measurement of PAH-DNA seems to be reasonable when the airborne sources of PAH predominate, whereas measuring 1-HP in urine in case of low level of the exposure to airborne PAH is more appropriate for evaluation of other sources of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have previously observed an association between PAH exposure and birth outcomes such as birth weight, child length, head and chest circumference and ratio of head circumference to birth weight [1][2][3][4][5][6][7][8][9][10][11]. Most nine [18][19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations